The Universal Brotherhood In Islamic Law: A Study Of The Thoughts Of Yusuf Al-Qaradawi And Ahmad Syafii Maarif - Yaqin, Nasrullah Ainul (UIN Sunan Kalijaga Yogyakarta, 2024)
Islamic radicalism and sectarianism conflicts between fellow Muslims not only destroy the peaceful life of mankind, but also damage the reputation of Islam. This paper discusses the concept of universal brotherhood in Islamic law according to the thoughts of Yusuf al-Qaradawi and Ahmad Syafii Maarif. It is a literature study and is descriptive-analytic-comparative using the usul al-fiqh approach. The results of this paper show that Yusuf al-Qaradawi and Ahmad Syafii Maarif both emphasize the obligation of Islamic law. They emphasize the obligation to carry out universal brotherhood in Islamic law, both brotherhood among Muslims (al-ukhuwwah ad-diniyyah) and brotherhood of fellow human beings (al-ukhuwwah al-basyariyyah). This is based on the Qur'an surah Al-Hujurat (49): 10 & 13 and several hadith. Al-Hujurat (49): 10 indicates the existence of brotherhood among Muslims. Therefore, Muslims must unite and help each other and should not be divided. should not be divided. As for Al-Hujurat (49): 13 indicates the existence of brotherhood among human beings. It emphasizes the equality of human dignity because all humans come from the same origin. Therefore, the brotherhood of fellow human beings has three elements that must be fulfilled, namely: love, equality, and mutual help. Yusuf al-Qaradawi calls the concept of universal brotherhood in Al-Hujurat (49): 10 and 13 as one of the great Islamic principles championed by Islam, while Ahmad Syafii Maarif calls it Qur'anic ethics. Both figures use the at-tafsir bi al-ma'śur method in interpreting Al-Hujurat (49): 10 and 13. This article contributes to the development of the understanding of Islamic law on the importance of maintaining Islamic and universal peace and brotherhood derived from contemporary thinkers. Radikalisme Islam dan konflik sektarianisme antarsesama muslim tidak hanya menghancurkan kedamaian hidup umat manusia, tetapi juga merusak citra baik Islam. Tulisan ini membahas konsep persaudaraan universal dalam hukum Islam menurut pemikiran Yusuf al-Qaradawi dan Ahmad Syafii Maarif. Ia merupakan kajian literatur dan bersifat deskriptif-analitik-komparatif menggunakan pendekatan ilmu usul al-fiqh. Hasil tulisan ini menunjukkan bahwa Yusuf al-Qaradawi dan Ahmad Syafii Maarif sama-sama menekankan kewajiban melaksanakan persaudaraan universal dalam hukum Islam, baik persaudaraan sesama muslim (al-ukhuwwah ad-diniyyah) maupun persaudaraan sesama manusia (al-ukhuwwah al-basyariyyah). Hal ini berdasarkan Al-Qur’an surah Al-Hujurat (49): 10 & 13 dan beberapa hadis. Al-Hujurat (49): 10 menunjukkan adanya persaudaraan sesama muslim. Oleh karena itu, umat Islam harus bersatu dan saling bantu sama lain serta tidak boleh berpecah belah. Adapun Al-Hujurat (49): 13 menunjukkan adanya persaudaraan sesama manusia. Ia menekankan persamaan martabat manusia karena semua manusia berasal dari asal-usul yang sama. Oleh karena itu, persaudaraan sesama manusia ini memiliki tiga unsur yang harus dipenuhi, yaitu: cinta, persamaan, dan saling tolong. Yusuf al-Qaradawi menyebut konsep persaudaraan universal dalam Al-Hujurat (49): 10 dan 13 sebagai salah satu prinsip agung Islam yang diperjuangkan oleh Islam, sedangkan Ahmad Syafii Maarif menyebutnya sebagai etika Al-Qur’an. Kedua tokoh tersebut sama-sama menggunakan metode at-tafsir bi al-ma’śur dalam menafsirkan Al-Hujurat (49): 10 dan 13. Artikel ini berkontribusi pada pengembangan pemahaman hukum Islam atas pentingnya menjaga perdamaian dan persaudaraan Islam maupun universal yang bersumber dari pemikir kontemporer.